Viral Marketing: Utilizing Digital Content Digitization to Enhance Brand Awareness, Brand Trust, and Customer Loyalty in Coffee Shops - Ida Bagus Wibisana Sudarta; Luh Putu Mahyuni (Eduvest - Journal of Universal Studies, 2024)
This study delves further into the use of viral marketing to boost customer loyalty, brand awareness, and brand trust in coffee shops. By looking at two case studies of coffee businesses that use influencer engagement and organic viral marketing tactics, a qualitative approach is used. By using two case studies with distinct approaches, we hope to shed light on how viral marketing can be successfully applied in a variety of situations. Eleven informants' interview data are evaluated through the use of coding and theming techniques. The study concludes that while the Story, Hype, Actionable, Relevant, and Emotional (SHARE) strategy is applied in both circumstances, the first case, which takes an organic approach, achieves higher levels of trust in the generated content than the influencer-involved case. Furthermore, the study reveals that the utilization of viral marketing tactics in conjunction with the SHARE concept has the potential to enhance consumer awareness, trust, and loyalty. This study makes a valuable contribution by providing in-depth understandings of the ways in which viral marketing can be utilized to improve consumer loyalty, brand awareness, and brand trust. It also closes a gap in the literature by explaining how Viral Marketing strategies can be strengthened through the application of the SHARE concept.